2008
DOI: 10.1128/mcb.02032-07
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the PDK1 PH Domain Inhibits Protein Kinase B/Akt, Leading to Small Size and Insulin Resistance

Abstract: PDK1 activates a group of kinases, including protein kinase B (PKB)/Akt, p70 ribosomal S6 kinase (S6K), and serum and glucocorticoid-induced protein kinase (SGK), that mediate many of the effects of insulin as well as other agonists. PDK1 interacts with phosphoinositides through a pleckstrin homology (PH) domain. To study the role of this interaction, we generated knock-in mice expressing a mutant of PDK1 incapable of binding phosphoinositides. The knock-in mice are significantly small, insulin resistant, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
154
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(166 citation statements)
references
References 64 publications
12
154
0
Order By: Relevance
“…The specific binding of the pleckstrin homology domain of PKB with PtdIns(3,4,5)P 3 becomes rate limiting for the translocation of PKB to the plasma membrane and colocalization with PDK1, where PDK1 can then efficiently phosphorylate PKB at Thr308 (28,29), while mTORC2 phosphorylates the Ser473 site in the hydrophobic motif (21), resulting in maximal activation of the enzyme. The significance of the interaction of the PDK1 PH domain with phosphoinositides in the activation of PKB has been evaluated in vivo using PDK1 K465E/K465E knock-in mice (30), which express a rationally designed point mutant form of PDK1 that retains catalytic activity but is incapable of phosphoinositide binding (27). In tissues derived from these mice, PKB is still activated by growth factors albeit to a reduced level (30)(31)(32), whereas the activation of the rest of the PDK1 substrates proceeds normally.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The specific binding of the pleckstrin homology domain of PKB with PtdIns(3,4,5)P 3 becomes rate limiting for the translocation of PKB to the plasma membrane and colocalization with PDK1, where PDK1 can then efficiently phosphorylate PKB at Thr308 (28,29), while mTORC2 phosphorylates the Ser473 site in the hydrophobic motif (21), resulting in maximal activation of the enzyme. The significance of the interaction of the PDK1 PH domain with phosphoinositides in the activation of PKB has been evaluated in vivo using PDK1 K465E/K465E knock-in mice (30), which express a rationally designed point mutant form of PDK1 that retains catalytic activity but is incapable of phosphoinositide binding (27). In tissues derived from these mice, PKB is still activated by growth factors albeit to a reduced level (30)(31)(32), whereas the activation of the rest of the PDK1 substrates proceeds normally.…”
mentioning
confidence: 99%
“…The significance of the interaction of the PDK1 PH domain with phosphoinositides in the activation of PKB has been evaluated in vivo using PDK1 K465E/K465E knock-in mice (30), which express a rationally designed point mutant form of PDK1 that retains catalytic activity but is incapable of phosphoinositide binding (27). In tissues derived from these mice, PKB is still activated by growth factors albeit to a reduced level (30)(31)(32), whereas the activation of the rest of the PDK1 substrates proceeds normally. As a consequence, these mice are smaller, prone to diabetes (30), and protected from PTEN-induced tumorigenesis (32).…”
mentioning
confidence: 99%
“…Normally PIP 3 , the second messenger of PI3K, recruits Akt and PDK1 to the plasma membrane via their PH domains. The current study suggests that Akt or PDK1 or both fail to be recruited onto the plasma membrane and thus Akt is inefficiently phosphorylated (30). Prior studies have shown that when a mutation was created in the PH domain of PDK1 at serine 241 to alanine, it resulted in a 50-fold decrease in the phosphorylation and activation of Akt (31).…”
Section: Genders Of Agpat2mentioning
confidence: 99%
“…Platelet-specific PDK1-deficient mice exhibit thrombocytopenia and inhibition of platelet aggregation and Akt activation (Chen et al, 2013). Moreover, the disruption of the PH domain in PDK1 knockin embryoid bodies resulted in impairment of Akt activation, vessel formation, and EC migration (Primo et al, 2007;Bayascas et al, 2008). Likewise, depletion of AMI GO2 using siRNA resulted in inhibition of PDK1 localization to the plasma membrane as well as activation and caused defective EC survival, It is well established that the PI3K-mediated PDK1-Akt signaling pathway plays a crucial role in regulating tumorigenesis and angiogenesis through VEGF and several other growth factors (Jiang and Liu, 2008;Meuillet et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…5 D). Because the PH domain of PDK1 binds to PIP3 and activates Akt signaling (Bayascas et al, 2008), we examined the direct binding of the AMI GO2 CD (AMI GO2 CD ) and the PDK1 PH domain (PDK1 PH ). As anticipated, His-PDK1 PH proteins, but not His-PDK1 kinase , could bind to GST-AMI GO2 CD under cellfree conditions (Fig.…”
Section: The Ami Go2 CD Interacts With the Pdk1 Ph Domainmentioning
confidence: 99%